2022
DOI: 10.3390/ma15238531
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Aqueous Media on the Corrosion Behavior of B4C-Modified Lightweight Al-Mg-Si Matrix Composites

Abstract: In this study, we have investigated the electrochemical corrosion behavior of boron carbide (B4C) ceramic-reinforced Al-Mg-Si matrix composites in various aqueous environments (NaOH, NaCl, HCl, and H2SO4). The samples were produced by the powder metallurgy (P/M) route and the corrosion investigations were conducted by potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS) methods. The morphology of the as-prepared and corroded samples was examined by scanning electron microscopy (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Materials 2024, 17, x FOR PEER REVIEW 15 of 20 value suggests weaker corrosion resistance [30]. From Table 3, it can be seen that as the NSS corrosion time increases from 0 to 144 h, the Ecorr value decreases.…”
Section: Electrochemical Test Results Of the Composite Materials At D...mentioning
confidence: 98%
See 1 more Smart Citation
“…Materials 2024, 17, x FOR PEER REVIEW 15 of 20 value suggests weaker corrosion resistance [30]. From Table 3, it can be seen that as the NSS corrosion time increases from 0 to 144 h, the Ecorr value decreases.…”
Section: Electrochemical Test Results Of the Composite Materials At D...mentioning
confidence: 98%
“…The E corr and I corr values can be obtained from the PDP curve for Table 3 . The E corr value serves as a thermodynamic criterion for the corrosion resistance of the composite material; a higher E corr value indicates stronger corrosion resistance, while a lower E corr value suggests weaker corrosion resistance [ 30 ]. From Table 3 , it can be seen that as the NSS corrosion time increases from 0 to 144 h, the E corr value decreases.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Ujah et al [13] showed that MWCNTs-reinforced aluminum alloy, produced by means of spark plasma sintering, exhibited a refined microstructure, high mechanical strength, and improved corrosion performance, as compared with the pure metal matrix sample, which could be attributed to the homogeneous dispersion of the MWCNTs in the matrix. Although the corrosion behavior in the research cited above was evaluated by potentiodynamic polarization curves, other corrosion techniques, such as electrochemical impedance spectroscopy (EIS), could be employed to evaluate the performance of the metal matrix composite's passive layer [14,15].…”
Section: Introductionmentioning
confidence: 99%